If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2a+73=-4a+19
We move all terms to the left:
2a+73-(-4a+19)=0
We get rid of parentheses
2a+4a-19+73=0
We add all the numbers together, and all the variables
6a+54=0
We move all terms containing a to the left, all other terms to the right
6a=-54
a=-54/6
a=-9
| x+7=-9→x=16 | | 3n-I=8 | | 8n^2+5=21 | | -13z+(-3z)=32 | | 12x+x=180−x | | 783=27g | | 2x-16+9x=72 | | –9−8b=–7b | | 19=-24(4+z)-3 | | 3=-w/5 | | 2x^2-3x-22=x^2-12 | | 4x+x=74 | | 4j=732 | | 6y+29=-5(y+3) | | 2x-5x+4=(-3x+4 | | -48=m12 | | 5+4c=9 | | 6x+2=7+2x+8x+7 | | -48=m12 | | 8n+15=55 | | -3(w-7)+2w=17 | | 306=9s | | 3x-18=-16+16x | | q(-4)=24 | | b+1/2-b=2b+1/4 | | 3x-18=-16-16x | | 6(y−1)= | | 644=28t | | 5n+5(2n-7)=-95 | | m(-7)=-28 | | –37-7x=6–4(4+4x) | | 2x-10+x+x+50=360 |